(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The scientific research considers the complex nomination – composites of terminological character in the modern language of medicine. The author analyzes the adjective terms and phrases. An assessment of such multi-formations and semantic and structural features and secularities of functioning are emphasized.